ANALISIS FAKTOR YANG MENYEBABKAN MENURUNNYA MINAT BELAJAR MATEMATIKA PADA MATERI PECAHAN SISWA KELAS IV SDN SIBREH - Aminah, Siti; Maulidar, Maulidar; Suryawati, Indah (Jurnal Dedikasi Pendidikan, 2025)
The aim of this research is to determine the factors causing low interest in learning mathematics in fractions. The approach used in this research is a qualitative approach. "Qualitative research is research that intends to understand the phenomena experienced by research subjects holistically. This type of research is descriptive, where descriptive research is a research method that shows the characteristics of the population or phenomenon being studied. Factors that cause a decrease in interest in learning mathematics in fraction material in class IV-b at Sibreh State Elementary School. The results showed that there were 4 students (50%) who did not pay attention when the teacher explained. From the results of the questionnaire obtained (47%) students were interested in taking part in mathematics lessons on fractions. And 70.23% of students agreed that learning mathematics on fractions was difficult to understand. Based on research results, the factors that cause low interest in learning mathematics in fraction material for class IV students at SDN Sibreh, namely in mathematics lessons, consist of teacher, parent and friend factors. Teachers use less media in learning and focus more on using printed books, so that students do not master the lesson